The Influence of Lifestyle, Perceived Price, and Instagram on Purchasing Decisions at Rumah Ngopi Cibinong - Muhamad Genta Ramadhan; Suryani Chodidjah (Formosa Journal of Applied Sciences, 2023)
This study aims to determine the effect of lifestyle, price perceptions, and Instagram on purchasing decisions. The study population is people who make purchases at Rumah Ngopi Cibinong. This research method uses quantitative research with a total of 101 respondents. Primary data was collected through a questionnaire using the Likert scale model and processed with SPSS 20. The results of this study are that simultaneously lifestyle, price perceptions, and Instagram influence purchasing decisions at Rumah Ngopi Cibinong.